2020
DOI: 10.3389/fphar.2020.00803
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin-3, 3′-Digallate Suppresses RANKL-Induced Osteoclastogenesis and Attenuates Ovariectomy-Induced Bone Loss in Mice

Abstract: Theaflavin-3, 3′-digallate (TF3) is extracted from black tea and has strong antioxidant capabilities. The aim of this study was to assess the influences of TF3 on osteoclastogenesis and explore the underlying mechanisms. TF3 efficiently decreased receptor activator of nuclear factor-kappa B ligand (RANKL)-induced osteoclast formation and reactive oxygen species (ROS) generation in a dose-dependent manner. Mechanistically, TF3 reduced ROS generation by activating nuclear factor erythroid 2-related factor 2 (Nrf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…OS was evaluated by detecting intracellular ROS generation, malondialdehyde (MDA) levels, and superoxide dismutase (SOD) activity. 25 Intracellular ROS were detected using an ROS Assay Kit (Beyotime) in this study. After treatment, cells in 24-well plates were incubated with 0.1% DCFH-DA diluted in α-MEM at 37°C for 25 min.…”
Section: Detection Of Osmentioning
confidence: 99%
“…OS was evaluated by detecting intracellular ROS generation, malondialdehyde (MDA) levels, and superoxide dismutase (SOD) activity. 25 Intracellular ROS were detected using an ROS Assay Kit (Beyotime) in this study. After treatment, cells in 24-well plates were incubated with 0.1% DCFH-DA diluted in α-MEM at 37°C for 25 min.…”
Section: Detection Of Osmentioning
confidence: 99%
“…A previous study has demonstrated that theaflavins, especially TF-3, attenuate oxidative stress and inflammation (6). TF-3 also has been indicated to decrease the incidence of coronary heart disease, exhibit an advantageous effect on the bone mineral density and the potential to prevent cancer (7)(8)(9). However, the effect of TF-3 in protecting against cigarette smoke extract (CSE)-induced pulmonary emphysema and the mechanism of action remains unclear.…”
Section: Theaflavin-33'-digallate Attenuates Cigarette Smoke Extract-induced Pulmonary Emphysema In Mice By Suppressing Necroptosismentioning
confidence: 99%
“…In the process of osteoporosis, the abnormality of bone metabolism is mainly caused by the decrease of bone formation and the increase of bone resorption. In Ai’s study, it reported that TFDG could reduce the activation of osteoclasts by inhibiting oxidative stress, ultimately improving osteoporosis ( Ai et al, 2020 ). However, the effect of TFDG on bone formation is not clear.…”
Section: Discussionmentioning
confidence: 99%